Ta có: \(\dfrac{-x^2+4x-10}{x^2+1}\)
= \(\dfrac{-\left(x^2-4x+4\right)-6}{x^2+1}\)
= \(\dfrac{-\left(x-2\right)^2-6}{x^2+1}\)
Mà -(x-2)2 \(\le\) 0 <=> -(x - 2)2 -6 \(\le\) 6 < 0
Và x2 \(\ge\) 0 <=> x2 +1 \(\ge\) 1 > 0
=> Ta thấy phân số đó có tử bé hơn 0 và mẫu lớn hơn 0
=> Phân số đó là phân số âm
Hay \(\dfrac{-x^2+4x-10}{x^2+1}\) < 0 với mọi x
Đúng 0
Bình luận (0)
vì \(x^2\ge0\) nên \(x^2+1\ge1>0\) (1)
\(-x^2+4x-10=-\left(x-2\right)^2+\dfrac{24}{-4}\le-6< 0\)(2)
từ (1) và (2) suy ra \(\dfrac{-x^2+4x-10}{x^2+1}< 0\)(đpcm)
Đúng 0
Bình luận (0)